A Methods engineering study on ICS-KWIKPRINT - Dela Cruz, Ma. Alesandra K. (College of Engineering, 1999)
The principal objective of this study is to evaluate and improve selected key areas in the production and operation department of ICS-Kwikprint. Basically, the study is divided into two major areas. The first area of study is the book publication area (Part I) and the second area of study is the systems and procedures area (Part II). In Part I, the SAPADAPPA method was used for preliminary evaluation. Two major problems were pointed out by the SAPADAPPA procedure. The first concerns the high rate of delays in production completion (Problem I) and the second concerns the poor flow of materials within the production area (Problem II). Further analysis revealed that Problem I is a result of the unavailability of time standards while Problem II is being caused by a poor facility layout. A work study was performed by the researchers to give an in-depth and quantitative assessment of the two major problems. Alternatives were generated and evaluated. The generation and evaluation of alternatives involved two major work study techniques, namely, methods study (for problem II) and work measurement (for problem I). In part II, a systems and procedures analysis was performed by the researchers. Critical areas were checked and improvements were made. Primarily, the systems and procedures analysis was done because the researchers believe that production activities are highly dependent on the company's systems and procedures. Finally, recommendations are summarized and an implementation program is presented.